2003
DOI: 10.1021/bi026596f
|View full text |Cite
|
Sign up to set email alerts
|

C2 Domain of Protein Kinase Cα:  Elucidation of the Membrane Docking Surface by Site-Directed Fluorescence and Spin Labeling

Abstract: The C2 domain is a conserved signaling motif that triggers membrane docking in a Ca 2+ -dependent manner, but the membrane docking surfaces of many C2 domains have not yet been identified. Two extreme models can be proposed for the docking of the protein kinase Cα (PKCα) C2 domain to membranes. In the parallel model, the membrane-docking surface includes the Ca 2+ binding loops and an anion binding site on β-strands 3-4, such that the β-strands are oriented parallel to the membrane. In the perpendicular model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
94
1
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 45 publications
9
94
1
3
Order By: Relevance
“…Biophysical studies have shown that the ␤-hairpin formed by ␤ strands 3 and 4 of the PKC␣ C2 domain lies close to the plasma membrane because of a nearly parallel orientation of the domain relative to the membrane (Kohout et al, 2003), similar to earlier predictions (Verdaguer et al, 1999). Further structural studies of PKC␣C2 complexed with Ca 2ϩ and soluble PS have revealed a basic region comprised of four lysine residues in the ␤3-4 hairpin that endow the region with a strong positive charge (Ochoa et al, 2002).…”
Section: Role Of the Basic Region In The ␤3-4 Hairpin In Targeting Tosupporting
confidence: 70%
See 3 more Smart Citations
“…Biophysical studies have shown that the ␤-hairpin formed by ␤ strands 3 and 4 of the PKC␣ C2 domain lies close to the plasma membrane because of a nearly parallel orientation of the domain relative to the membrane (Kohout et al, 2003), similar to earlier predictions (Verdaguer et al, 1999). Further structural studies of PKC␣C2 complexed with Ca 2ϩ and soluble PS have revealed a basic region comprised of four lysine residues in the ␤3-4 hairpin that endow the region with a strong positive charge (Ochoa et al, 2002).…”
Section: Role Of the Basic Region In The ␤3-4 Hairpin In Targeting Tosupporting
confidence: 70%
“…For example, our earlier work has shown that the CBLs of a related C2 domain from cPLA 2 were sufficient to promote the native intracellular targeting of this C2 domain, which docks to Golgi and ER membranes in vivo (Evans et al, 2004). Furthermore, other studies have suggested that residues located in the PKC␣ C2 domain CBLs are important in targeting of the isolated C2 domain to the plasma membrane (Conesa-Zamora et al, 2001;Stahelin et al, 2003;MarinVicente et al, 2005), and biophysical studies of PKC␣C2 docking have demonstrated that the CBLs directly contact the membrane surface (Kohout et al, 2003; Figure 1A).…”
Section: Intracellular Targeting and Lipid Binding Of Hybrid C2 Domaimentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is becoming evident that insertion of proteins into membranes is widespread, the three-dimensional orientations and quantitative binding properties remain challenging to characterize. The most common electron paramagnetic resonance and fluorescence approaches have provided important insights (17)(18)(19)(20) but require covalent attachment of paramagnetic groups to various positions of the protein or mutations of residues. The inevitable effects of these modifications on lipid interactions indicate a need to develop new methods that provide quantitative measures of bilayer insertion by native proteins.…”
mentioning
confidence: 99%